Konsep Pendistribusian Kekayaan Menurut Al-Quran - Taufik Hidayat (AL-FALAH : Journal of Islamic Economics, 2017)
Wealth according to the Qur'an: Distribution of current income is a very important thing. If the income distribution is not appropriate to do, then most of the income and resources would be controlled by the capitalist monopolies, resulting in many people remain in poverty despite the country having abundant resources. On these basic considerations can be affirmed that the welfare and prosperity of the people depend on the way how it should be equitable distribution system could be implemented. Islam as a source of value to combine economic development with the religious sector. The activities of distribution of goods and services and income, shall use a value judgment mechanistic determinism of Islam and not the other economic systems such as capitalism and socialism. Separation of positive and normative values lead to human economic activity economic destructive animal. The economic crisis that hit the Indonesian economy is the impact of the application of the system of political, legal, social system, education and the economy are not in accordance with value, impact on damage to ecosystems, forests, water pollution and the environment, and the process of structural poverty.